2005
DOI: 10.1021/tx050196m
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship for Noncoplanar Polychlorinated Biphenyl Congeners toward the Ryanodine Receptor-Ca2+ Channel Complex Type 1 (RyR1)

Abstract: Ryanodine receptor isoforms are expressed in both excitable and nonexcitable tissues where they form microsomal Ca2+ release channels broadly involved in shaping cellular signaling. In this report, we provide a detailed structure-activity relationship (SAR) for polychlorinated biphenyl (PCB) congeners and metabolites necessary for enhancing ryanodine receptor type 1 (RyR1) activity using [3H]ryanodine ([3H]Ry) binding analysis. The 2,3,6-Cl PCB configuration is most important for optimal recognition by the RyR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
220
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(230 citation statements)
references
References 60 publications
10
220
0
Order By: Relevance
“…For example, Crofton (1996) described a SAR study of 14 different triazole fungicides which cause hyperactivity in rats. A QSAR for PCB neurotoxicity (Pessah et al, 2005), based on data for 28 ortho-substituted PCBs, and building on earlier work (Nevalainen et al, 1994), revealed a relationship between electronic descriptors (E LUMO , E HOMO , the E LUMO −E HOMO gap, and molecular polarizability) and the binding affinity of PCBs to the aryl hydrocarbon (Ah) receptor. In particular, impairment of the developing nervous system by PCBs has been linked to their ability to alter the spatial and temporal fidelity of Ca2+ signalling in muscle and nerve cells through one or more receptor-mediated processes (Pessah et al, 2009).…”
Section: Neurotoxicitymentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Crofton (1996) described a SAR study of 14 different triazole fungicides which cause hyperactivity in rats. A QSAR for PCB neurotoxicity (Pessah et al, 2005), based on data for 28 ortho-substituted PCBs, and building on earlier work (Nevalainen et al, 1994), revealed a relationship between electronic descriptors (E LUMO , E HOMO , the E LUMO −E HOMO gap, and molecular polarizability) and the binding affinity of PCBs to the aryl hydrocarbon (Ah) receptor. In particular, impairment of the developing nervous system by PCBs has been linked to their ability to alter the spatial and temporal fidelity of Ca2+ signalling in muscle and nerve cells through one or more receptor-mediated processes (Pessah et al, 2009).…”
Section: Neurotoxicitymentioning
confidence: 93%
“…Chan et al (2008c) rat hepatocyte toxicity α,β-unsaturated aldehydes 11 Chan et al (2007) human and rat hepatocyte toxicity halobenzenes 12 Pessah et al (2005) developmental neurotoxicity ( …”
mentioning
confidence: 99%
“…Noncoplanar PCBs have two or more ortho-chlorine substitutions and very weak or no aryl hydrocarbon receptor-binding activity. Recent studies find that noncoplanar PCBs are potent sensitizers of ryanodine receptor (RyR) calcium channels (5)(6)(7)(8)(9) and, as such, affect Ca 2ϩ release from intracellular stores (7)(8)(9)(10) and influence the cellular response to both chemical and electrical signals (11,12). RyRs, previously thought to exist only in muscle tissue, now are documented in both pre-and postsynaptic terminals in neurons in many brain areas (13)(14)(15); RyRs were shown to affect neuronal excitability (13,(15)(16)(17)(18)(19)(20)(21)(22) and synaptic plasticity, modulating both long-term potentiation and long-term depression (13,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Prominent examples are the polyaromatic hydrocarbons that mediate their toxicity through the arylhydrocarbon receptor (AhR), such as dioxin, or through selective interactions with ryanodine receptors (RyR) in the brain (Zimanyi and Pessah, 1991), such as non-coplanar polychlorinated biphenyls (PCBs). Interactions of non-coplanar PCBs with RyR greatly sensitize the release of Ca 2+ from the microsomal intracellular stores (Wong et al,1997;Pessah et al,2006), and are likely to contribute to imbalances in excitatory and inhibitory neurotransmission and the abnormal development of brain circuitry (Kenet et al, 2007; and review below by Lein). Sensitization of RyRs by PCBs has been shown to be responsible for a host of toxicological outcomes in vitro including amplification of NMDA-mediated excitation and Ca 2+ /caspase mediated apoptosis (Gafni et al,2004;Wong et al, 2001;Howard et al, 2003).…”
Section: Chemicals That Interfere With Calcium (Ca 2+ ) Signalingmentioning
confidence: 99%